Alone : Britain, Churchill, and Dunkirk : defeat into victory - Korda, Michael, 1933- (Liveright Publishing Corporation, a division of W. W. Norton & Company, 2017)
"Combining epic history with rich family stories, Michael Korda chronicles the outbreak of World War II and the great events that led to Dunkirk. In an absorbing work peopled with world leaders, generals, and ordinary citizens who fought on both sides ofWorld War II, Alone brings to resounding life perhaps the most critical year of twentieth-century history. For, indeed, May 1940 was a month like no other, as the German war machine blazed into France while the supposedly impregnable Maginot Line crumbled, and Winston Churchill replaced Neville Chamberlain as prime minister in an astonishing political drama as Britain, isolated and alone, faced a triumphant Nazi Germany. Against this vast historical canvas, Michael Korda relates what happened and why, and also tells his own story, that of a six-year-old boy in a glamorous movie family who would himself be evacuated. Alone is a work that seamlessly weaves a family memoir into an unforgettable account of a political and military disaster redeemed by the evacuation of more than 300,000 men in four days--surely one of the most heroic episodes of the war. "The incredible, almost miraculous story of what happened at Dunkirk in the year 1940--and why--is unfolded in Alone with great narrative skill and superb delineation of a highly interesting cast of characters, including, importantly, the author himself and his own remarkable family." -- David McCullough